2021
DOI: 10.1111/sum.12702
|View full text |Cite
|
Sign up to set email alerts
|

Soil quality and fertility in sustainable agriculture, with a contribution to the biological classification of agricultural soils

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 171 publications
0
7
0
1
Order By: Relevance
“…As an important component in soil N cycling, the bacterial community connected soil function and plant productivity under specific environmental conditions in agricultural ecosystems [ 88 ]. Exogenous input, for instance, chemical fertilizer and organic materials, can shift bacterial community and their subsequent functional behavior [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an important component in soil N cycling, the bacterial community connected soil function and plant productivity under specific environmental conditions in agricultural ecosystems [ 88 ]. Exogenous input, for instance, chemical fertilizer and organic materials, can shift bacterial community and their subsequent functional behavior [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al [ 93 ] also reported that excessive N application in grain fields accelerated N loss via leaching or to the atmosphere based on a meta-analysis using 1174 paired observations from 69 publications. Sofo et al [ 88 ] stated that organic inputs in combination with reduced fertilizer input could decrease N loss via greenhouse gas emission and leaching.…”
Section: Discussionmentioning
confidence: 99%
“…However, they observed significantly lower concentrations of exchangeable potassium and extractable phosphorus in organically managed soils. These studies show that management practices impact soil fertility and should be considered by farmers, land managers, and crop advisers in the decision-making processes to choose appropriate agricultural practices (Sofo et al, 2022).…”
Section: Highlightsmentioning
confidence: 98%
“…NPs may also affect soil fauna, such as earthworms and nematodes (Huerta Lwanga et al, 2016). Earthworms could promote plant development by modifying the soil environment, like enhancing soil permeability, enzyme activity and nutrients (especially effective phosphorus; Carlesso et al, 2022; Sofo et al, 2022; Wang et al, 2019). However, numerous researches demonstrated that high concentration of MPs adversely affect the survival, growth rate, cast production, digging and feeding behaviour of earthworms (Liu et al, 2021).…”
Section: Implications For Soil Health Managementmentioning
confidence: 99%